Impact of mobile applications on participation of retail investors in Indian stock market - Shivani,; Thakur, Shivani; Godara, Tamanna (The journal of contemporary issues in business and government, 2022)
Over the last few years, Stock markets around the world has witnessed major changes in terms of participation of retail investors. One of the key factors behind these changes is the availability of investing opportunities via online and mobile trading. With reduced transaction cost and ease of access, stock markets have become almost within a reach of hand, especially for retail investors. We find that financial technology has enabled more small investors to enter into the stock market than the large investors because of low cost and ease of access.